Luminous Procuress - Jepson, Warner (Second Run, 2022)
"The only feature film by artist, mystic and polymath Steven Arnold, Luminous Procuress is a bold, experimental, mind-and-gender-bending odyssey of unabashed hedonism. A celebration of otherness, of pan-sexuality, and of the exotic, Luminous Procuress is a truly unique work of Art. Often compared to the works of Fellini and Kenneth Anger, and featuring the outrageous talents of San Francisco's avant garde drag troupe The Cockettes, as well as artist ruth weiss, the film was an underground sensation upon release, but disappeared from circulation for many years. Now fully restored in all its sensuous glory, Luminous Procuress is ready to be discovered anew." [arrowfilms.com]"
Original: USA 1971
Special features: presented from an HD transfer of the new 2K restoration of the fully uncut version of the film by the UC Berkeley Art Museum and Pacific FIlm Archive, and the Cinema Preservation Alliance ; newly-filmed interview with producer Harry Tsvi Strauch discussing the film and director Steven Arnold ; curator and author Steve Seid on the history and preservation of Luminous procuress ; 24-page booklet featuring an essay by Steve Seid and new writing by film scholar/critic Elena Gorfinkel ; world premiere release on Blu-ray
Bildformat 1.37:1
Keywords: Film; Blu-Ray-Disc